Thymosin ?4: a multi-functional regenerative peptide. Basic properties and clinical applications - Goldstein, Allan L.; Hannappel, Ewald; Sosne, Gabriel; Kleinman, Hynda K. (Expert Opinion on Biological Therapy, 2012)
INTRODUCTION: Thymosin ?(4), a low molecular weight, naturally-occurring peptide plays a vital role in the repair and regeneration of injured cells and tissues. After injury, thymosin ?(4), is released by platelets, macrophages and many other cell types to protect cells and tissues from further damage and reduce apoptosis, inflammation and microbial growth. Thymosin ?(4) binds to actin and promotes cell migration, including the mobilization, migration, and differentiation of stem/progenitor cells, which form new blood vessels and regenerate the tissue. Thymosin ?(4) also decreases the number of myofibroblasts in wounds, resulting in decreased scar formation and fibrosis. AREAS COVERED: This article will cover the many thymosin ?(4) activities that directly affect the repair and regeneration cascade with emphasis on its therapeutic uses and potential. Our approach has been to evaluate the basic biology of the molecule as well as its potential for clinical applications in the skin, eye, heart and brain. EXPERT OPINION: The considerable advances in our understanding of the functional biology and mechanisms of action of thymosin ?(4) have provided the scientific foundation for ongoing and projected clinical trials in the treatment of dermal wounds, corneal injuries and in the regeneration and repair of heart and CNS tissue following ischemic insults and trauma.
EVALuna2:4923